2016
DOI: 10.1186/s13000-016-0473-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing diagnostic accuracy to grade dysplasia in Barrett’s esophagus using an immunohistochemical panel for CDX2, p120ctn, c-Myc and Jagged1

Abstract: BackgroundPatients with non-dysplastic Barrett’s esophagus (ND-BE) and low-grade dysplasia (LGD) are typically monitored by periodic endoscopic surveillance, while those with high-grade dysplasia (HGD) and esophageal adenocarcinoma (EAC) are usually treated by more aggressive interventions like endoscopic mucosal resection, ablation or surgery. Therefore, the accurate grading of dysplasia in Barrett’s esophagus (BE) is essential for proper patient care. However, there is significant interobserver and intraobse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…MYC is another major transcriptional target of β‐catenin. Similar to CCND1, immunochemical staining showed weaker nuclear expression for MYC in BE and low‐grade dysplasia samples compared to HGD and EAC …”
Section: Ctnnb1 In Be Progressionsupporting
confidence: 67%
See 1 more Smart Citation
“…MYC is another major transcriptional target of β‐catenin. Similar to CCND1, immunochemical staining showed weaker nuclear expression for MYC in BE and low‐grade dysplasia samples compared to HGD and EAC …”
Section: Ctnnb1 In Be Progressionsupporting
confidence: 67%
“…Similar to CCND1, immunochemical staining showed weaker nuclear expression for MYC in BE and low-grade dysplasia samples compared to HGD and EAC. 92 Surprisingly, the presence of abnormal ␤-catenin (including loss of membranous staining and the appearance of nuclear staining) in tissue samples of EAC patients correlates with better survival. 84 The reason behind this observation is not clear, but it is consistent with similar observations in colorectal cancer, where obese patients positive for nuclear ␤-catenin had significantly better overall survival, 93 and in medulloblastoma, where the WNT signature molecular subgroup has the best prognosis.…”
Section: Ctnnb1 In Be Progressionmentioning
confidence: 96%
“…The performance of the system was better than that of the general pathologist and only slightly inferior to that of the experienced pathologist. In addition, there were still some studies using immunohistochemical indicators only[ 43 ] or the characteristics of nuclear DNA structure and organization combined with DNA ploidy analysis[ 44 ] to grade BE dysplasia, but the results were not satisfactory. Therefore, HE stained pathological image features supplemented by relevant immune indicators or other image enhancement techniques may be the main direction of AI-assisted pathological diagnosis in the future.…”
Section: Ai In Pathological Diagnosis Of Early Ecmentioning
confidence: 99%
“…Presence of Barrett's esophagus with high-grade dysplasia (HGD) is considered the best predictor for the development of esophageal adenocarcinoma. Six to sixty percent of HGD cases can progress to EAC each year [3] . However, large previous studies confirmed that patients who are diagnosed as BE with low grade dysplasia (LGD) have five times higher risk of development of EAC in comparison to those with non-dysplastic BE (ND-BE) [1] .…”
Section: Introduction In Barrett's Esophagus (Be) or Barrett's Metaplasia Squamous Epithelial Lining Of The Esophagus Ismentioning
confidence: 99%